Pengaruh Model Pembelajaran Numbered Heads Together (NHT) Terhadap Hasil Belajar Matematika Siswa Kelas III SD - Septia Pelelawati Purba; Ribka Kariani Sembiring; Antonius Remigius Abi; Rumiris Lumban Gaol; Darinda Sofia Tanjung; Yohanes Suhardin; Elizabeth Ghozali (Departement of Mathematics Education, 2024)
This research is a type of quantitative research. The research was conducted at SD Negeri 060883 Jln. Darusalam, Kec. Medan Petisah. This study amounted to 23 students based on saturated sample technique. Student learning outcomes showed that the average value of pre-test class III students was 44.60 while the Post-test value was 77.60. Furthermore, hypothesis testing shows that the tcount is 4.666 while the ttable is 1.721, it is proven that the hypothesis is greater than the ttable, so Ho is rejected and Ha is accepted. This shows that there is an effect of the Numbered Heads Together (NHT) learning model on student learning outcomes.